CRAMER’S RULE IN INTERVAL MIN-PLUS ALGEBRA - Siswanto, Siswanto; Septiany, Ade Safira (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
A min-plus algebra is a set , where is the set of all real numbers, equipped with the minimum and addition operations. The system of linear equations in min-plus algebra can be solved using Cramer's rule. Interval min-plus algebra is an extension of min-plus algebra, with the elements in it being closed intervals. The set is denoted by equipped with two binary operations, namely minimum and addition . The matrix with notation is a matrix over interval min-plus algebra with size . Since the structure of min-plus algebra and interval min-plus algebra are analogous, the system of linear equations in interval min-plus algebra can be solved using Cramer's rule. Based on the research results, the sufficient conditions of Cramer's rule in interval min-plus algebra are for , and . The Cramer rule is .